Damage Deformation of Flexure-Yielding Steel-Reinforced Concrete Coupling Beams: Experimental and Numerical Investigation - Yinghui Li; Huanjun Jiang; T. Y. Yang (Advances in Civil Engineering)
SRC coupling beams offer many significant advantages, including the reduction in section depth, reduced congestion at the wall boundary region, improved degree of coupling for a given beam depth, and improved deformation capacity. In this paper, 7 half-scale flexure-yielding SRC coupling beams designed according to Chinese approach have been tested under cyclic loads. Detailed parameters such as aspect ratios, steel reinforcement ratios, and steel flange-web ratios were systematically studied, and the damage behavior of SRC coupling beams were presented in this paper. The test results show that the aspect ratio, steel ratio, and steel flange-web ratio have great influence on the damage behavior of SRC coupling beams. Three-dimensional nonlinear finite element models were constructed and benchmarked through comparison with test results for both global and local damage deformation behavior. Based on the material damage and strength degradation, four performance levels were defined and corresponding chord rotation limits were obtained through the verified numerical analysis.